Combined Urea Complexation and Argentated Silica Gel Column Chromatography for Concentration and Separation of PUFAs from Tuna Oil: Based on Improved DPA Level. (27th May 2016) - Mu, Hongyan; Jin, Jun; Xie, Dan; Zou, Xiaoqiang; Wang, Xiaosan; Wang, Xingguo; Jin, Qingzhe
Abstract: Eicosapentaenoic acid (EPA, 20:5n‐3), docosapentaenoic acid (DPA) isomers (22:5n‐6 and 22:5n‐3) and docosahexaenoic acid (DHA, 22:6n‐3) derived from tuna oil were concentrated by three stages of urea fractionation at various crystallization temperatures and different fatty acid/urea ratios. Thereafter, polyunsaturated fatty acids concentrate containing comparatively enriched DPA levels was purified by argentated silica gel column chromatography. A product containing 22.2 ± 0.6 % EPA, 4.6 ± 0.0 % DPAn‐6, 5.9 ± 0.1 % DPAn‐3 and 42.3 ± 1.2 % DHA was obtained at 1:1.6 fatty acid/urea ratio (w/w) by crystallization at −8 °C for 16 h, −20 °C for 8 h, and −8 °C for 16 h. A DPA isomer concentrate containing 26.1 ± 0.5 % DPAn‐6 and 22.3 ± 0.4 % DPAn‐3 was achieved by argentated silica gel chromatography in the 6 % acetone/ n ‐hexane solvent fraction (v/v), and the recovery of both fatty acids was 66.1 ± 3.2 and 70.7 ± 2.2 %, respectively. Furthermore, 91.9 ± 2.5 % EPA and 99.5 ± 2.1 % DHA with recoveries of 47.8 ± 2.0 and 56.7 ± 3.3 %, respectively, were obtained in various fractions.